Simulointeja yhteisöveron alennuksen dynaamisista vaikutuksista Suomessa; Simulating the Dynamic Effects of Corporate Income Tax Cut in Finland - Tarmo Valkonen; Eija Kauppi; Paavo Suni (The Research Institute of the Finnish Economy (ETLA), 2014)
– This study simulates with two dynamic models the macroeconomic and public finance outcomes of a reduction in the corporate income tax rate in Finland. FOG-model is a dynamic CGE model, which is calibrated to the Finnish economy. NiGEM is a multi-country macroeconometric model. The results show that a surprising cut in the corporate income tax rate falls after all adjustments both on new investments and the yield of existing capital. The losses in the tax revenues are capitalized in the market value of the firms, of which many are partly foreign-owned. Investments increase, but the influence in production is mitigated by low reaction of labour supply. Wages increase as well as the public expenditure relates to wages. Gross profits do dot change much. The dynamic effects on tax bases compensate for 30–50 per cent of the losses in the corporate income tax revenues, depending on the model used. If also the increased public expenditure is considered, the compensation rate falls to 25–30 percent. If the tax rate cut is announced well in advance, both the macroeconomic and the public finance results are more favourable. The simulations do not consider the positive effects of profit shifting on corporate income tax revenues.
Keywords: H22; H25; C54; C68; 330; Corporate and capital income taxation; Dynamic effects; CGE model; Macroeconometric model; Körperschaftsteuer; CGE-Modell; Makroökonomisches Modell; Finnland